Beyond crisis: understandings of vulnerability and its consequences in relation to intimate partner ciolence - Zimmermann, Nesa (Human rights review, 2023)
This article takes a closer look at intimate partner violence (IPV) and its semantical, political, and legal interactions with crisis and crisis discourse. Starting from the fact that IPV has been called a “shadow pandemic” and a “hidden crisis”, the article conceptualizes two parallel phenomena: how the COVID-19 pandemic — and crises in general — impact on IPV by exacerbating vulnerabilities and how crisis discourse has been mobilized to argue for a responsive state and strong positive obligations to combat and reduce IPV. The article then draws a parallel between crisis discourse and vulnerability reasoning, analyzing how vulnerability has played a similar role within the case law of the European Court of Human Rights (ECtHR) and led the latter to develop a consistent strand of case law concretizing states’ positive obligations. The article also takes a critical stance, examining the risks of crisis discourse and vulnerability when viewed through a crisis lens. To counter these risks, it argues for a nuanced, structural, and dynamic understanding of vulnerability and a focus on resilience-building institutions and mechanisms. Within the ECtHR case law, this signifies elaborating upon the already existing positive obligations, including by taking inspiration from the Council of Europe Convention on preventing and combating violence against women and domestic violence (Istanbul Convention). Such an approach is necessary to leave behind the emergency time usually associated with crises and work toward lasting structural change.